Transitioning from Analogue to Digital Radio Broadcasting: A Simulcast System Approach in Indonesia - ., Harliantara; Widiarto, Didik Sugeng; Prasetyo, Iwan Joko; Wahyuanto, Eko; Sjuchro , Dian Wardiana (Journal of Ecohumanism, 2025)
The Indonesian government’s initiative to transform digital radio broadcasting has commenced, facilitating the transition from analogue to digital radio transmission via a simulcast system. Comprehensive implementation of these technological changes has the potential to yield optimal digital radio broadcasting ecosystems. A distinguishing attribute of this simulcast system is its capacity to transmit analogue and digital frequencies concurrently. Despite its considerable practical relevance, there is a paucity of systematic knowledge regarding the reasons why analogue and digital radio broadcast simulcast systems must be implemented to maintain pace with the development of broadcasting technology in this digital age. This research contributes to the future of radio broadcasting by exploring the ecosystem factors of a multiplatform simulcast broadcast model. This analysis is grounded in a qualitative examination of the simulcast system (both analogue and digital) within the Internet sector of the broadcast industry. The research identifies several factors: first, terrestrial analogue radio; second, terrestrial digital radio; third, Internet radio and human resources; fourth, analogue and digital simulcast systems; and fourth, Internet multi-social media platforms.